2021
DOI: 10.1039/d1ra02673a
|View full text |Cite
|
Sign up to set email alerts
|

Polymer films doped with fluorescent sensor for moisture and water droplet based on photo-induced electron transfer

Abstract: Polymer films doped with a photo-induced electron transfer (PET)-type fluorescent sensor exhibit green excimer emission in the PET active state, but blue monomer emission in the PET inactive state upon exposure to moisture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…2b and c). Therefore, these facts indicate that the fluorescence properties of EN-1 in both the aggregate state and the solid state were not derived from the anthracene dimer or excimer emission 17,18 but were due to the AIE characteristics associated with the aggregate formation of EN-1(H 2 O)-A in both the PET-inactive and RIR states (Fig. 1c).…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…2b and c). Therefore, these facts indicate that the fluorescence properties of EN-1 in both the aggregate state and the solid state were not derived from the anthracene dimer or excimer emission 17,18 but were due to the AIE characteristics associated with the aggregate formation of EN-1(H 2 O)-A in both the PET-inactive and RIR states (Fig. 1c).…”
Section: Resultsmentioning
confidence: 93%
“…[1][2][3][4][5][6][7][8][9][10][11] Moreover, fluorescent sensors for water have the potential to be functional materials, which would allow the visualization as well as detection and quantification of moisture or water droplets on material surfaces, and have promise to be applied to environmental, biomedical, and quality control monitoring systems. [12][13][14][15][16][17][18] Indeed, various kinds of organic fluorescent sensors for the determination of the water content in solvents based on their intramolecular charge transfer (ICT), [19][20][21][22][23][24][25][26][27][28][29] excited state intramolecular proton transfer (ESIPT), [30][31][32][33] photoinduced electron transfer (PET) [34][35][36][37][38][39][40][41] or solvatofluorochromic properties [42][43][44][45][46]…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, concern has been raised about the development of fluorescent sensors and their functional materials such as polymer films and sensor-immobilized membranes for visualizing water in solutions, solids, and gas or on material surfaces, from the viewpoint of their potential applications to environmental and quality control monitoring systems and industry, as well as fundamental study in photochemistry, analytical chemistry, and photophysics. 1–23 Several investigations have been conducted on the design and synthesis of organic fluorescent sensors and polymers for the detection of water based on ICT (intramolecular charge transfer), 24–34 ESIPT (excited state intramolecular proton transfer), 35–38 PET (photo-induced electron transfer), 39–46 or solvatochromism 47–52 and the elucidation of the optical sensing properties based on changes in wavelength, intensity, and lifetime of fluorescence emission depending on the water content. It was demonstrated that most of ICT- and ESIP-type fluorescent sensors and fluorescent conjugated polymers exhibited attenuation of the fluorescence emission, that is, fluorescence quenching (turn-off) systems with the increase in water content in solvents, and were suitable for the detection and quantification of a trace amount of water (below 1–10 wt% in almost every case) in solvents.…”
Section: Introductionmentioning
confidence: 99%